Fracto-surface mobility mechanism in high-strength steel wires. (December 2017) - Sanchez, J.; Fullea, J.; Andrade, C.
Highlights: The Stress Corrosion Cracking Surface Mobility Theory is modified. It is made an integration of fracture mechanics into the Surface Mobility theory. Vacancies are driven by a stress gradient in non-stationary conditions. Crack arrest cases are explained. Abstract: Stress corrosion cracking, a mechanism governing steel deterioration, has yet to be fully understood. This article introduces a supplement to the surface mobility mechanism proposed by Galvele to include fracture mechanics principles. In the model proposed, anodic dissolution is regarded as the source of vacancies that would be driven by a stress gradient to the crack tip under non-stationary conditions. Denominated the fracto-surface mobility mechanism (FSMM), it explains material mechanical failure based on vacancy diffusion across the metal surface.